From Story to Loyalty: The Impact of Storytelling in Social Media Marketing on Loyalty to Local Fashion Brands in Jakarta - Prastowo, Kurniadi; Nurmulya, Fitrasyah (Jurnal Industri Kreatif dan Kewirausahaan, 2025)
This study aims to examine the effect of Social Media Marketing (SMM) on Brand Loyalty by considering the mediating roles of Brand Image and Brand Storytelling in local fashion brands in Jakarta. Data were collected from 120 active social media users and consumers of local fashion brand products through a questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that SMM has a significant effect on Brand Image and Brand Storytelling, but does not directly influence Brand Loyalty. Instead, Brand Image and Brand Storytelling act as mediators that strengthen the relationship between SMM and consumer loyalty. These findings highlight the importance of narrative-based social media strategies to enhance brand image and foster consumer loyalty toward local fashion products.